Characterization, testing, measurement, and metrology - Davim, J. Paulo; Prakash, Chander; Singh, Sunpreet , 1989- (Boca Raton, FL : CRC Press, 2020)
"This book presents the broad aspects of measurement, performance analysis, and characterization for materials and devices by advanced manufacturing processes. The field of measurement and metrology as a pre-condition for maintaining high quality products/devices/systems in materials and advanced manufacturing process applications has grown strongly over the past years. The focus of this book is to present in numerous technological sectors, smart materials in automotive, bio-manufacturing, chemicals, electronics, energy, and construction materials. The advanced materials, which are progressing nowadays, have novel properties, thus must be fully characterized and studied, in-depth, so they can be incorporated into products that out-perform existing problems. The book has capture emerging areas of materials science and advanced manufacturing engineering and presents the recent trends in research for young researchers, field engineers, and academic professionals"-- Provided by publisher
Includes bibliographical references (184-185 pages) and index
Keywords: Materials -- Testing